2021
DOI: 10.3389/fpubh.2021.679711
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Ageism During the Covid-19-Crisis Is Longitudinally Related to Subjective Perceptions of Aging

Abstract: Ageism in media and society has increased sharply during the Covid-19-crisis, with expected negative consequences for the health and well-being of older adults. The current study investigates whether perceived ageism during the crisis longitudinally affects how people perceive their own aging. In June 2020, N = 611 older adults from Luxembourg [aged 60–98 years, Mage(SD) = 69.92(6.97)] participated in a survey on their perception of the crisis. In October 2020, N = 523 participated in a second measurement occa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…This very universal trend toward more negative ATOA could be due to the described one-sided portrayals of older adults a one homogeneous vulnerable risk group during the pandemic and due to cases of “COVID ageism” (Kessler & Bowen, 2020), as observed, for instance, in social media (Jimenez-Sotomayor et al, 2020; Meisner, 2021; Xiang et al, 2021). As a consequence, middle-aged and older adults could have internalized and integrated such age stereotypes into their self-perceptions of aging, and such an internalization process is in line with stereotype embodiment theory (Levy, 2009) as well as with empirical findings (Brothers et al, 2021; Kornadt et al, 2021b). Alternatively, it might be the role of the pandemic as a stress trigger (Bäuerle et al, 2020; Brakemeier et al, 2020; Gilan et al, 2020; Munk et al, 2020; Peters et al, 2020; Petzold et al, 2020) that might have caused a shift toward more negative perceptions of aging, as greater stress has been found to be associated with less favorable views on aging (Wettstein et al, in press).…”
Section: Resultssupporting
confidence: 72%
“…This very universal trend toward more negative ATOA could be due to the described one-sided portrayals of older adults a one homogeneous vulnerable risk group during the pandemic and due to cases of “COVID ageism” (Kessler & Bowen, 2020), as observed, for instance, in social media (Jimenez-Sotomayor et al, 2020; Meisner, 2021; Xiang et al, 2021). As a consequence, middle-aged and older adults could have internalized and integrated such age stereotypes into their self-perceptions of aging, and such an internalization process is in line with stereotype embodiment theory (Levy, 2009) as well as with empirical findings (Brothers et al, 2021; Kornadt et al, 2021b). Alternatively, it might be the role of the pandemic as a stress trigger (Bäuerle et al, 2020; Brakemeier et al, 2020; Gilan et al, 2020; Munk et al, 2020; Peters et al, 2020; Petzold et al, 2020) that might have caused a shift toward more negative perceptions of aging, as greater stress has been found to be associated with less favorable views on aging (Wettstein et al, in press).…”
Section: Resultssupporting
confidence: 72%
“…Moreover, the potential mechanism of the association between perceived stigma and quality of life remains inconclusive. Previous studies confirmed that age-based stereotypes, prejudice, and discrimination harmed older adults, thus severely limiting opportunities to secure their health, well-being, and quality of life (8).…”
Section: Relationship Of Self-perceived Stigma and Quality Of Lifementioning
confidence: 90%
“…Especially in the digital age, there is a growing gap between older and younger individuals regarding values, thoughts, and lifestyles (6). Further, whereas social forces driven by the transformation of new media, social networking technology, and marketing strategies contribute to encouraging youth-centered lifestyle, they shape negative attitudes toward aging and elicit adverse depictions regarding older adults and the aging process (7,8). Numerous older adults also struggle with multiple dilemmas and are often stereotyped as forgetful, useless, lonely, and unattractive (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing several studies from different sources, ageism seems to be growing as the COVID-19 pandemic continues [18][19][20][21]. At the same time, a strong call from international organisations (such as WHO [22]) demanding public and private social agents for anti-ageism movements, policies and actions has been spread around the world.…”
Section: Introductionmentioning
confidence: 99%